Community Use and Product Valuation of Forest Resources in Maasai Mau - Koech, Charles Kiprono; Njuguna, Jane W.; Kiama, Stephen M.; Mau, James O.; Kaigongi, Magrate M.; Muganda, Michael M.; Nadir, Stanley; Kigomo, John N.; Cheboiwo, Joshua (Advances in Social Sciences Research Journal, 2021)
Forests play an important role in the livelihoods of local people in most developing countries. Local communities depend on forest resources for various products such as fuel wood, construction materials, medicine, and food. The Maasai Mau forest plays an important role in supporting the livelihood of people living around the forest. Exploitation of forest resources should only be limited to active members. To reduce dependency on the forest, alternative means of livelihood should be provided to reduce dependency on the forest.